2018
DOI: 10.1111/sms.13039
|View full text |Cite
|
Sign up to set email alerts
|

Slow movement resistance training using body weight improves muscle mass in the elderly: A randomized controlled trial

Abstract: To examine the effect of a 12-week slow movement resistance training using body weight as a load (SRT-BW) on muscle mass, strength, and fat distribution in healthy elderly people. Fifty-three men and 35 women aged 70 years old or older without experience in resistance training participated, and they were randomly assigned to a SRT-BW group or control group. The control group did not receive any intervention, but participants in this group underwent a repeat measurement 12 weeks later. The SRT-BW program consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 15 publications
0
36
0
1
Order By: Relevance
“…To overcome the limitation, Watanabe et al (39) examined BWRE with tonic force generation during slow movement (BWRE-slow) in older adults, and found that this RE improved muscle strength. Tsuzuku et al (37) also found that BWRE-slow improved muscle strength in the elderly, accompanied by muscle hypertrophy. BWRE-slow can be conducted easily in any setting within a small space and attenuate hypertension during RE.…”
Section: Introductionmentioning
confidence: 93%
“…To overcome the limitation, Watanabe et al (39) examined BWRE with tonic force generation during slow movement (BWRE-slow) in older adults, and found that this RE improved muscle strength. Tsuzuku et al (37) also found that BWRE-slow improved muscle strength in the elderly, accompanied by muscle hypertrophy. BWRE-slow can be conducted easily in any setting within a small space and attenuate hypertension during RE.…”
Section: Introductionmentioning
confidence: 93%
“…Resistance training is the requirement to generate force to move or resist weight such as weight lifting/push ups/leg press. Numerous studies have shown beneficial effects of resistance training in the function of skeletal muscle of older people; increasing muscle mass and strength (Fiatarone et al 1994 ; Maltais et al 2015 ; Tsuzuku et al 2018 ) as well as cross-sectional area of myofibres (Fiatarone et al 1994 ; Leenders et al 2013 ; Ribeiro et al 2017 ) and motility (Fiatarone et al 1994 ; Liu and Latham 2009 ).…”
Section: Resistance Trainingmentioning
confidence: 99%
“…Exercise may be a treatment alternative to drugs to slow functional declines in dementia. In healthy older adults, both aerobic and strength exercises are associated with improvements in cognitive functions such as executive function, inhibitory control and episodic memory [3][4][5], and physical functions, i.e., muscle strength, balance, functional reach, mobility, and endurance [4,[6][7][8][9]. Regrettably, the effects of exercise on these cognitive and physical functions in PwD have been inconsistent [5,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%